A review on capital punishment in Malaysia with reference to murder cases / Khairul Anuar Ismail - Ismail, Khairul Anuar (2014)
Capital punishment has been an issue of debate for decades. It refers to the practice of executing someone as punishment for a specific crime after a proper legal trial. It is usually used as a punishment for serious crimes such as murder but in some countries treason and drug trafficking am also capital crimes. This study examines the arguments and issues related to capital punishment especially for murder cases. This study will also make comparative analysis between some of the countries that are still practising, had abolished and reintroduced capital punishment. The qualitative method of study is used for this research. From the analysis of this study it suggests that as-to-date, 58 countries still retain capital punishment while 98 countries had abolished it. Palestine. Taiwan and Thailand had re- introduced capital punishment after years of moratorium. From the analysis of this study also. 11 suggests that the common arguments for capital punishment arc retribution, deterrence, the right to life, the risk of executing the innocence and public opinion; with public opinion being regarded as the most influential argument. Furthermore, factors such as pressure from the international organizations, government’s political orientation, economic development, background of the offender and religion are said to heavily influence the capital punishment’s policy and practice of countries.